독립적인 전력 콜랩스 방법론 - KOOB CHRISTOPHER EDWARD; PYLA MANOJKUMAR; LESTER ROBERT ALLAN; ZHONG PEIXIN; CHEN XUFENG (2017)
반도체 장치의 피처 크기는 새로운 세대 마다 계속 감소하고 있다. 더 작은 채널 길이들은 누설 전류의 증가로 이어진다. 누설 전류를 감소시키기 위해, 디바이스 내의 일부 전력 도메인들은 비활성의 기간들 동안 전력 차단될 수 있다(예를 들어, 전력 콜랩스됨). 그러나 콜랩스된 도메인들로 전력이 리턴할 때, 다른 전력 도메인들의 회로는 새롭게 전력공급된 도메인들에 대한 통신 채널들을 재구성하는 것과 연관된 상당한 프로세싱 오버헤드를 경험할 수 있다. 데이터 연결들을 재설정하는 것과 연관된 프로세싱 오버헤드를 보다 잘 관리하면서 유연한 전력 콜랩스를 조장하도록 전력 도메인을 격리하기 위한 예시적인 기술이 본 개시에서 제공된다. The feature size of semiconductor devices continues to decrease in each new generation. Smaller channel lengths lead to increased leakage currents. To reduce leakage current, some power domains within a device may be powered off (e.g., power collapsed) during periods of inactivity. However, when power is returned to the collapsed domains, circuitry in other power domains may experience significant processing overhead associated with reconfiguring communication channels to the newly powered domains. Provided in the present disclosure are exemplary techniques for isolating power domains to promote flexible power collapse while better managing the processing overhead associated with reestablishing data connections.